2008
DOI: 10.1111/j.1365-2818.2008.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection of luminescence from semiconductor quantum dots by nanosecond time‐gated imaging with a colour‐masked CCD detector

Abstract: SummaryQuantum dots are of considerable interest as highly detectable labels with broad absorption, narrow spectral emission and good quantum yields. The luminescence emission has a longer decay time than that of the most common fluorophores, leading to facile rejection of much background emission (such as autofluorescence from biological samples) by means of gated detection. Here, it is shown that a new technique, true-colour nanosecond time-gated luminescence imaging, can be used for selective detection of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…In practice this means that the smaller the QD, the bluer the light. In general, QDs have a relatively long lifetime, which provides the possibility to correct for background signals from short lived fluorescent species by time-gating techniques [ 33 , 34 ]. In addition, it was recently shown that the size of the QD also determines the lifetime, which increases with size [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In practice this means that the smaller the QD, the bluer the light. In general, QDs have a relatively long lifetime, which provides the possibility to correct for background signals from short lived fluorescent species by time-gating techniques [ 33 , 34 ]. In addition, it was recently shown that the size of the QD also determines the lifetime, which increases with size [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can maintain high brightness even after repeated cycles of excitation and fluorescence for hours. Therefore, background signals from short-lived fluorescent species can be corrected by time-gating techniques, allowing QDs be used for long-term monitoring and cell-tracking studies [25, 26]. Second, each QD has a quite broad absorption spectrum and a narrow and symmetrical emission spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Designing FLIM probes with longer lifetimes may prevent these effects [ 258 ]. Here, the usage of quantum dots with long fluorescence lifetimes may be an alternative [ 259 ]. Another challenge in using FLIM-FRET probes arises in experiments where the probes are overexpressed by cells.…”
Section: Challenges and Limitationsmentioning
confidence: 99%